2016
DOI: 10.1596/1813-9450-7785
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregating the Impact of the Internet on International Trade

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 10 publications
4
18
1
1
Order By: Relevance
“…Along the same lines, Tay (2015) has found a strong and positive effect of the Internet on trade in educational services. In line with previously highlighted studies, Osnago and Tan (2016) have observed that the Internet adoption influences positively international trade, although bilateral exports are more affected when Internet adoption increases in the exporting country than the importing country. Abeliansky and Hilbert (2017) have investigated the differential effects of telecommunication quantity (data subscriptions per capita) and quality (bandwidth data speed per subscription) of fixed and mobile telephony and internet services on countries' bilateral goods exports.…”
Section: Theoretical Motivation: Effect Of the Internet On Tax Revenusupporting
confidence: 90%
“…Along the same lines, Tay (2015) has found a strong and positive effect of the Internet on trade in educational services. In line with previously highlighted studies, Osnago and Tan (2016) have observed that the Internet adoption influences positively international trade, although bilateral exports are more affected when Internet adoption increases in the exporting country than the importing country. Abeliansky and Hilbert (2017) have investigated the differential effects of telecommunication quantity (data subscriptions per capita) and quality (bandwidth data speed per subscription) of fixed and mobile telephony and internet services on countries' bilateral goods exports.…”
Section: Theoretical Motivation: Effect Of the Internet On Tax Revenusupporting
confidence: 90%
“…This is in line with empirical studies that have shown that access to the internet improves export performance in developing countries across manufacturing and services sectors through reduced search costs and decreased distance barriers (Clarke, 2008, Freund andWeinhold, 2004;Hortaçsu et al, 2009;Ahn et al, 2011;and Lendle et al, 2016). Further the internet has also been shown to increase firm productivity, especially of smaller and less innovative firms (Clarke and Wallsten, 2006;Lin, 2015;Osnago and Tan, 2016;Paunov and Rollo, 2016).…”
Section: Introductionsupporting
confidence: 82%
“…Using a panel of 200 countries between 1990 and 2006, Lin (2015) found that Internet use reduced information costs in international trade, obtaining results similar to those of Choi (2010). Osnago and Tan (2016) examined data from 2001 to 2013 and found that higher Internet use by both exporters and importers increased trade value. Similar results were obtained in studies specifi c to China.…”
mentioning
confidence: 75%